HUBUNGAN ANTARA TINGKAT PENGETAHUAN DAN SIKAP DENGAN TINDAKAN WANITA USIA SUBUR DALAM PEMERIKSAAN PAYUDARA SENDIRI (SADARI) (DI DESA SOBA KECAMATAN AMARASI BARAT KABUPATEN KUPANG) - Loisa Eunike Sakan (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2020)
Breast self-examination (BSE) is an examination technique where a woman checks her own breasts by looking and feeling with her fingers to detect whether there are lumps or not on her breasts. This research is a quantitative study and the research method used here is cross sectional. The number of respondents in this study were 80 people with Convenience Sampling technique. The instrument used was a questionnaire. The results showed that most respondents had good knowledge about breast self-examination there are 40 people (50%) and quite good knowledge about breast self-examination which was 40 people (50%). Respondents have a good attitude regarding breast self-examination there are 68 people (85%) and the respondent's good enough attitude toward breast self-examination is 12 people (15%).Respondents have good actions about breast self-examination there are 15 people (18%) and quite good actions regarding breast self-examination there are 65 people (81%). The statistical test results using the Spearman Rho test were obtained p-value = 0,000 (ρ <0.05), the conclusion H0 was rejected, meaning that there is a relationship between the level of knowledge and attitude with the actions of fertile age woman in breast self-examination (BSE). Keywords: Knowledge level, attitude, breast self-examination action